Interpersonal Dynamics as Argumentative Force between Aznar and Zapatero - Espejo Muriel, María del Mar (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article analyses the State of the nation debates corresponding to the President Aznar (2001 – 2003) and Zapatero (2005 – 2011). Enunciative polyphony is the research method used to study the discursive strategies that intervene in the preservation of identity of the speaker in its different functions, especially in the development of the alternation of roles. To do this, this article addresses textual productions that combine verbal structures narrated in the singular and plural form of the first person. The results show that the speaker’s image intersubjectivity, as the most responsible agent over his own speech, is part of an argumentative construction that needs to be tackled. The pragmatic and communicative resources and strategies developed by image management are also a part of this analysis, focusing especially on the following functions: Ethos, Pathos and Logos.